Role of low-density lipoprotein receptor rs5925 (1959C>T) gene polymorphism in pathogenesis of dyslipidemia among Egyptian lupus nephritis patients - Yumn A. Alsabbagh,; Saher A. Ahmed,; Heba E. Salama,; Mai A. Abd-Elmawla,; Hala L. Elgendy, (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the prevalence of low-density lipoprotein receptor (LDL-R) rs5925 genetic variants and to evaluate their relationship with plasma lipid and kidney functions in lupus nephritis patients. Patients and methods: Between September 2020 and June 2021, a total of 100 lupus nephritis patients (8 males, 92 females; mean age: 31.1±1.1 years; range, 20 to 67 years) and a total of 100 age- and sex-matched healthy volunteers (10 males, 90 females; mean age: 35.8±2.8 years; range, 21 to 65 years) were included. The gene polymorphism rs5925 (LDLR) was performed by polymerase chain reaction-restriction fragment length polymorphism (PCR‐RFLP). Lipid profile and kidney functions were measured. Results: Regarding rs5925 (LDLR), C allele was significantly higher among lupus nephritis patients (60%) compared to the control group (45%). While T allele was significantly lower in lupus nephritis patients (40%), compared to the control group (p=0.003). The plasma level of total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C) were significantly lower in lupus nephritis patients with TT and CT genotypes, compared to those with CC genotype. Moreover, atherogenic index of plasma (AIP) and LDL-C/high-density lipoprotein cholesterol (HDL-C) ratio were significantly lower in patients with TT genotype, compared to the patients with CC genotype. There was a strong and clear association between patients with renal biopsies grades III & IV & V and LDLR C allele (p=0.01, p=0.003, and p=0.004, respectively). Conclusion: C allele is the significantly prevailed LDLR C1959T variant among lupus nephritis patients. Moreover, LDL-R genetic variant may be one of the non-immunological mechanisms implicated in the disturbed lipid profile among lupus nephritis patients. Profound dyslipidemia may partly underscore the deterioration of kidney function among lupus nephritis patients.